Surgical and prosthodontic treatment using alveolar distraction osteogenesis and implant placement for a patient with mandibular prognathism: A clinical report - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2007)
A 49-year-old patient presented with an Angle Class III malocclusion with a partially edentulous mandible, as diagnosed by orofacial examination and radiographic and cephalometric analyses. The patient refused orthognathic surgery; therefore, the treatment plan included the preparation of all teeth and fabrication of provisional restorations to reestablish optimal occlusion. To allow for the placement of 3 implants, the edentulous posterior mandibular ridge was improved via alveolar distraction. The patient was recalled 3, 6, 12, and 24 months after prosthodontic treatment. The oral situation was stable and patient satisfaction was reported as high.